2014
DOI: 10.1136/bjophthalmol-2013-304301
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography shows retinal abnormalities associated with optic nerve disease

Abstract: Optical coherence tomography (OCT) of the macula in patients with primary optic neuropathy has revealed the presence of structural changes in the neurosensory retina in addition to the nerve fibre layer. Subretinal fluid has been documented in papilloedema and non-arteritic ischaemic optic neuropathy, and may account for decreased visual acuity in affected patients. Subretinal fluid has also been described from other causes of optic nerve head swelling including diabetic papillopathy and papillitis. Drugs used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
(33 reference statements)
1
17
0
Order By: Relevance
“…This reflects differences in patient populations in academic centres, for example, caused by a productive neurosurgical department in Groningen. The presence of microcystic changes in the context of hydrocephalus as described in one of our patients is consistent with another recent report on bilateral microcystic changes in a child with bilateral optic atrophy due to hydrocephalus (see figure 5 in Tawse et al 19). …”
Section: Discussionsupporting
confidence: 93%
“…This reflects differences in patient populations in academic centres, for example, caused by a productive neurosurgical department in Groningen. The presence of microcystic changes in the context of hydrocephalus as described in one of our patients is consistent with another recent report on bilateral microcystic changes in a child with bilateral optic atrophy due to hydrocephalus (see figure 5 in Tawse et al 19). …”
Section: Discussionsupporting
confidence: 93%
“…Tawse et al . [15] in their comprehensive review on OCT changes observed in optic nerve diseases suggested that subfoveal subretinal fluid occurred in about 15% of patients with acute NAION and speculated about the source of the subretinal fluid. According to them subretinal fluid did not likely arise directly from the choroid or retinal vessels as fluorescein angiogram did not show any evidence of leakage.…”
Section: Discussionmentioning
confidence: 99%
“…OCT is emerging as a useful ancillary investigation and assessment of retinal nerve fibre layer (RNFL) thickness, with a peripapillary ring scan, and macular volume, were advocated in a recent expert consensus review [12]. OCT has identified additional pathological features, such as macular cystic changes in some patients [13]; the significance and nature of their pathophysiology is debated and a topic of further research. Cranial magnetic resonance imaging (MRI) is helpful to stratify risk of subsequent MS in clinically isolated T-ON-if the patient wishes to know-and to confirm the diagnosis of MS in people with a history of previous neurological episodes.…”
Section: T-on Is a Clinical Diagnosis And Ancillary Investigations Armentioning
confidence: 99%